OPTIMALISASI KONTEN PEMASARAN SEBAGAI STRATEGI MENINGKATKAN KEPUTUSAN PEMBELIAN DI E-COMMERCE: STUDI KASUS GLOGLOWING SKINCARE - Muhammad Amrulloh; Supriady Supriady; Rahma Hanum (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2026)
This study examines the optimization of digital marketing content as a strategy to enhance consumers’ purchase decisions on e-commerce platforms, using Gloglowing Skincare as the case study. Gloglowing Skincare is a local skincare brand based in Indramayu Regency, West Java, which markets its products through various digital platforms, including Shopee, TikTok Shop, and Instagram. Preliminary observations identified three main issues: (1) a lack of variation in internally managed marketing content, (2) limited use of original product photos in the e-commerce catalog, and (3) excessive reliance on influencer-generated content. Through a two-month internship program (July–August 2024), a series of strategic interventions were implemented, including the production of educational and promotional content, the creation of more than 20 professional product photos, and the development of a structured content calendar. The results indicate a significant positive impact: organically produced video content achieved over 473,000 views and 38,000 likes on TikTok without the support of paid advertising or influencers. These findings suggest that optimizing marketing content through internal production can effectively increase consumer engagement and directly drive purchase decisions. This study contributes to the practical understanding of content marketing strategies for small and medium enterprises (SMEs) in the beauty industry in the digital era.